2009
DOI: 10.1183/09031936.00094008
|View full text |Cite
|
Sign up to set email alerts
|

Pleural plaques and asbestosis: dose– and time–response relationships based on HRCT data

Abstract: Most studies on asbestos-related diseases are based on chest radiographs, and dose-response relationships are still controversial. The aim of this study was to describe the most relevant parameters of asbestos exposure linked to pleural plaques and asbestosis diagnosed by high-resolution computed tomography (HRCT).A large screening programme including systematic HRCT examinations was organised from 2003 to 2005 in France for formerly asbestos-exposed workers. The time since first exposure (TSFE), level, durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 33 publications
3
71
0
2
Order By: Relevance
“…For example, in one series of analyses TSFE, mean fiber concentration and cumulative exposure were found to be significant (Paris et al, 2008(Paris et al, , 2009. Various mathematical models have been suggested to describe the relationship between exposure and the prevalence of pleural plaques (Finkelstein & Vingilis, 1984;Järvholm, 1992;McDonald et al, 1986;Paris et al, 2008Paris et al, , 2009). …”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one series of analyses TSFE, mean fiber concentration and cumulative exposure were found to be significant (Paris et al, 2008(Paris et al, , 2009. Various mathematical models have been suggested to describe the relationship between exposure and the prevalence of pleural plaques (Finkelstein & Vingilis, 1984;Järvholm, 1992;McDonald et al, 1986;Paris et al, 2008Paris et al, , 2009). …”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%
“…Numerous studies have examined the dose-or exposureresponse relation for pleural plaques (Bar-Shai et al, 2012;Boffetta, 1998;Clin et al, 2011;Eisenhawer et al, 2014;Ehrlich et al, 1992;Finkelstein & Vingilis, 1984;Hosoda et al, 2008;Jakobsson et al, 1995;Järvholm, 1992;Karjalainen et al, 1994;Lockey et al, 2015;Mastrangelo et al, 2009;McDonald et al, 1986;Moolgavkar et al, 2014;Paris et al, 2008Paris et al, , 2009Rohs et al, 2008;Sandén & Järvholm, 1986;Shepherd et al, 1997;Soulat et al, 1999;Van Cleemput et al, 2001). Results differ among these studies, 6 but exposure variables found relevant in one or more studies include time since first exposure (TSFE), age at first exposure (Jones, 1997), type (Hillerdal, 1997;Jones, 1997;Sandén & Järvholm, 1986) and dimensions of fiber (Hillerdal, 1997;Jones, 1997), lung fiber burden (Karjalainen et al, 1994;Roberts, 1971), duration of exposure, intensity of estimated asbestos exposure and cumulative exposure (measured in various ways).…”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%
“…In the absence of a control group, demonstration of a significant relationship between pleural plaques and duration of exposure (used as a surrogate of cumulative exposure to asbestos) is an argument in favor of the causal role of asbestos (Paris et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only automobile mechanics with no other known occupational exposure to asbestos and with a sufficiently long latency (.20 years in 99% of cases, .30 years in 89% of cases) to allow evaluation of asbestos-related diseases, especially pleural plaques, were included in the study (Schwartz, 1991;Paris et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, connective tissue diseases-associated lung fibrosis is very common and sometimes leads the prognosis, such as in patients with systemic sclerosis or rheumatoid arthritis [13]. Asbestosis and chronic hypersensitivity pneumonitis are environmentinduced lung fibrotic diseases with a poor prognosis and limited therapeutic possibilities [14,15]. Idiopathic fibrotic nonspecific interstitial pneumonia is also a progressive fibrotic lung disease with a significant mortality, although it has a better prognosis than IPF [16].…”
mentioning
confidence: 99%